GOVERNMENT SUPPORT FOR SMALL AND MEDIUM-SIZED ENTERPRISES IN THE CONTEXT OF THE PANDEMIC: FOREIGN AND RUSSIAN PRACTICE - N. N. Musinova; N. S. Sergienko (Вестник университета, 2021)
Modernization of Russia involves a qualitative breakthrough in the sector of small and medium-sized businesses, using new technologies and developing an innovative sphere. The creation of a developed small and medium-sized enterprise can solve many modern Russian problems, so the state should develop small and medium-sized enterprises and, if necessary, support them. The need to support small and medium-sized enterprises has become particularly acute during the coronavirus pandemic and continues to be relevant both abroad and in the Russian Federation. The study of domestic and foreign experience in providing support to small and medium-sized businesses allowed us to highlight general and private forms of assistance.